The plants by Daniel Rolander (c. 1723-1793) in Diarium Surinamicum (1754-1765) and herbaria - Rodrigues De Moraes, Pedro Luis [UNESP]; Dobreff, James; Reinhammar, Lars Gunnar (Magnolia Press, 2014)
The manuscripts of Diarium Surinamicum by Daniel Rolander practically remained ignored and unpublished for over 240 years, till the recent publication of its translation into English, which occurred in 2008. In this, the names of species described and/or cited by Rolander were faithfully retained, hence preserving the indication of them without authorship, for the vast majority. In the present work, all the names of plants that were treated by Rolander in his journal, about 664, including by tradition the fungi and algae, are contextualised in relation to the authorship, reference to the publication of the protologue, pagination of citations/descriptions in the manuscripts and in the published translation, indication of probable misidentifications with possible alternative names, vernacular names, and related literature. Additionally, we searched for the vouchers collected by Rolander, scattered in several herbaria, which have been linked to the probable names and descriptions in the diary. Given the considerable time till the publication of these names, and by the lack of indication of their nomenclatural types in the English version, the great majority of the new species described by Rolander, which would have priority if published in due time, became invalid names according to the ICN. Nevertheless, the list of Rolandrian species here presented, from his work that has finally taken a place in the history of natural sciences, shows that he was also a competent botanist, besides being a skilled entomologist, having recognised and detailedly described many of the Surinamese plants hitherto unknown to science.
Keywords: Carl Linnaeus; Christen Friis Rottboll; historical collections; Peter Jonas Bergius; taxonomy; Surinamese flora